As mulheres de Nelson Rodrigues: a construção do conflito a partir das relações femininas - Salvático, Carolina Ubal [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Nelson Rodrigues is a controversial figure, known mostly for his revelation of human masks through the effective investigation of social ills in interpersonal relationships. With divergent and contradictory opinions, the playwright builds plays that border on the absurd, using revolutionary resources in the Brazilian theater scene (breaking with the classical figure while satirizing it). Based on the hypothesis that there is an obsession with the female gender in his works, the present project aims to explore how this aspect is fundamental in the construction of dramatic conflict, in order to understand the irony that permeates the characterization of female relationships. Therefore, the analysis intends to collate three plays by the playwright: Vestido De Noiva (1943), A Falecida (1953) e Os sete gatinhos (1958).

Nelson Rodrigues é uma figura polêmica, conhecido em grande parte por sua revelação das máscaras humanas através da efetiva investigação das mazelas sociais nas relações interpessoais. Com opiniões divergentes e contraditórias, o dramaturgo constrói peças que beiram o absurdo, se valendo de recursos revolucionários no cenário do teatro brasileiro (rompendo com a figura clássica enquanto a satiriza). Partindo da hipótese de que há uma obsessão pelo gênero feminino em suas obras, o presente projeto visa explorar como esse aspecto é fundamental na construção do conflito dramático, a fim de entender a ironia que permeia a caracterização das relações femininas. Para tanto, a análise pretende cotejar três obras do dramaturgo: Vestido De Noiva (1943), A Falecida (1953) e Os sete gatinhos (1958).
The women of Nelson Rodrigues: the framing of conflict based in female action
Keywords: Nelson Rodrigues; Teatro moderno; Personagem feminina